LOCALIZAÇÃO DE FÉRMIONS EM UM ANEL IMERSO EM (3,1) DIMENSÕES - Martins, Genilson Vieira (2012)
We studied the localization of fermionic fields in a ring-like topological defect constructed with a real scalar field ϕ and immersed in (3, 1)−dimensional spacetime. The process of localization of fermions in the ring is analyzed by studying a Yukawa-like coupling ¯ ΨF(ϕ)Ψ, where F(ϕ) is a function of the real scalar field. Using the usual γ−matrices in (1, 1)−dimensions, we express the Dirac spinor in terms of its chiral left-handed and right-handed components. The amplitudes of fermions support Schr¨odinger-like equations allowing a probabilistic interpretation of them. In our case, to analyze the existence of resonances, we consider the coupling F(ϕ) = (1 − ϕ2)2. The eigenvalue equations are solved using numerical procedures. The eigenvalues that characterize the resonances are obtained for the two chiralities that show exactly the same, confirming the qualitative analysis of the potential are supersymmetric partners.